FEKO/NEC2 Simulation of Candidate Antennas for the Long Wavelength Array (LWA) - Fekadu, Nassissie; Zaghloul, Amir I. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
This paper presents FEKO and NEC-2 simulations done on three dipole-like structures; the big blade, the tied-fork and the fork antenna. These antenna elements are considered for the design of the long wavelength array (LWA). The LWA is an interferometer under construction in New Mexico, USA for astronomical observations in the 20 - 80 MHz spectrum. This paper presents the simulation results of a co-polarized antenna gain patterns, impedance values, and mutual couplings for each candidate elements. Coupling results from FEKO and NEC-2 simulations are compared with measurement result of the big blade antenna. The paper also presents Sparameters for 25 elements of the tied-fork antennas.